Proximity to natural habitat is not consistently associated with pollination services in tropical smallholder farms: A systematic review and meta‐analysis - Bosshard, Ennia; Harrison, Mark E.; van Veen, Frank; Kettle, Chris; Chikkarangappa, Nagaraja Badenahally; Banks, John E.; Basu, Parthiba; Casiá‐Ajché, Quebin Bosbely; Dalsgaard, Bo; Dutta, Aditi; Enríquez, Eunice; Escobedo‐Kenefic, Natalia; et al. (Wiley, 2025)
ABSTRACT Proximity to natural habitat is known to enhance pollination services in large‐scale agriculture, but it remains unclear whether this holds in tropical smallholder farms. These systems are embedded in ecologically complex landscapes, central to global food security, and depend heavily on biodiversity‐derived ecosystem services. We conducted a systematic review and meta‐analysis of 35 studies assessing the relationship between distance to natural habitat and pollinator abundance, species richness, and crop fruit set in tropical smallholder farms. We found no consistent patterns in pollinator abundance and crop fruit set with increasing distance, with relationships highly variable across studies. Similarly variable, yet slightly negative, was the relationship between distance and pollinator species richness. Our findings suggest limited support for the ‘proximity to natural habitat’ hypothesis in tropical smallholder farms, indicating that the inherent complexity of these landscapes may buffer negative effects of distance on pollination. This underscores the importance of maintaining and restoring landscape complexity to sustain biodiversity and ecosystem services such as crop pollination. We also highlight the need for greater methodological consistency and publicly available raw data in future studies to strengthen the evidence base and support management strategies for safeguarding pollination services in tropical smallholder farms.